2018
DOI: 10.1103/physreve.98.062128
|View full text |Cite
|
Sign up to set email alerts
|

Critical dynamical exponent of the two-dimensional scalar ϕ4 model with local moves

Abstract: We study the scalar one-component two-dimensional (2D) φ 4 -model by computer simulations, with local Metropolis moves. The equilibrium exponents of this model are well-established, e.g. for the 2D φ 4 -model γ = 1.75 and ν = 1. The model has also been conjectured to belong to the Ising universality class. However, the value of the critical dynamical exponent z c is not settled. In this paper, we obtain z c for the 2D φ 4 -model using two independent methods: (a) by calculating the relative terminal exponentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
5
4
0
Order By: Relevance
“…We find that line magnetisation exhibits anomalous diffusion. Our results for anomalous diffusion is consistent with a pattern that the dynamics of magnetisation at the critical temperature in spin models is anomalous [21][22][23]. Importantly, the anomalous diffusion is described by the Generalised Langevin Equation (GLE) [22,23] (and bears strong resemblance to anomalous diffusion in polymeric and membrane systems under a variety of circumstances [3,5,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]), which we verify in Sec.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…We find that line magnetisation exhibits anomalous diffusion. Our results for anomalous diffusion is consistent with a pattern that the dynamics of magnetisation at the critical temperature in spin models is anomalous [21][22][23]. Importantly, the anomalous diffusion is described by the Generalised Langevin Equation (GLE) [22,23] (and bears strong resemblance to anomalous diffusion in polymeric and membrane systems under a variety of circumstances [3,5,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]), which we verify in Sec.…”
Section: Introductionsupporting
confidence: 88%
“…. , 10 for three different system sizes L = 120, 160, 200 (from our earlier works on spin systems [21][22][23] we expect that the data collapse would require scaling time with a prefactor (p/L) zc ). The solid line in the figure then represents…”
Section: Fourier Modes As Approximate Dynamical Eigenmodes Of the Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…The most well-known of these rules is the single-site update rule or Metropolis algorithm, which is consistent with experimental observations of the critical dynamics in an iron film [44]. The same value of z is found in the Hohenberg-Halperin model A dynamics [45] as well as in φ 4 -theory [46].…”
Section: Introductionsupporting
confidence: 80%
“…The most recent result by Zhong et al [50] for a two-dimensional scalar φ 4 model with local Metropolis updates seems to confirm the results for 2D Model A by Nightingale and Blöte from [7], as they find z A " 2.17p3q and z A " 2.19p3q for two different values of the coupling constant. Additionally, they demonstrated that quantities derived from the two-point function follow a scaling behaviour.…”
Section: Critical Dynamics and Scaling Functionssupporting
confidence: 72%